TCM in Canada: Health Care and the Importance of Alternative Medicines that Complement Medical Practice - Honoré France (Wolters Kluwer Health/LWW, 2022)
This article explores the introduction and growth of traditional Chinese medicine (TCM) through the lens of Chinese immigration to Canada. It further explores how it has spread to other cultural groups in Canada. Several theories are described to explain why it has attracted attention by non-Chinese ethnicities: the interest in organic and nature-based approaches, the underfunding health care, lack of family doctors, expensive drugs from big pharmaceutical companies, and respect for Chinese cultural practices. The regulatory practice of TCM is described along with the organization, types of educational program and certification as well as a patient's perspective of TCM treatment.